(untitled) (Journal of Asian Development Studies, 2025)
Curiosity plays a crucial role in higher education by stimulating students’ intrinsic motivation to explore, learn, and engage deeply with academic content. It positively influences both lifelong learning orientation and cognitive engagement, fostering sustained interest and strategic learning behaviors. The objectives of the study were a) to find the level of Curiosity, Students’ Lifelong Learning Orientation, and Cognitive Engagement in Higher Education, b) to investigate the influence of Curiosity on Students’ Lifelong Learning Orientation and Cognitive Engagement in Higher Education, and c) to examine correlation among Curiosity, Students’ Lifelong Learning Orientation and Cognitive Engagement in Higher Education. The study population included all public and private universities in Lahore district. The sample was selected from the population using a multistage sampling method. The instruments of the study were questionnaires. For data analysis, SPSS was used, including descriptive statistics (Mean and Standard Deviation) and inferential statistics (multivariate analysis, Kendall’s tau-b, Spearman’s rho, and Pearson’s r). The study’s findings revealed that Curiosity has a significant effect on students’ lifelong learning orientation and cognitive engagement in higher education, explaining 44.3% of the variance in lifelong learning orientation and 33.7% of the variance in cognitive engagement (p < .001). Curiosity is positively and significantly correlated with both lifelong learning orientation (ρ = .574, p < .001) and cognitive engagement (ρ = .471, p < .001), indicating that students with higher curiosity tend to adopt stronger lifelong learning attitudes and engage more deeply in cognitive tasks.